EP 86. Interneuron synaptopathy induced by the pro-inflammatory cytokine LIF in developing neocortex. Issue 9 (September 2016) - Engelhardt, M.; Hamad, M.I.K.; Patz, S.; Wirth, M.J.; Grabert, J.; König, J.; Jamann, N.; Jack, A.; di Cristo, G.; Maffei, L.; Berardi, N.; Wahle, P.
Abstract : An inflammatory episode during brain development is discussed as first hit which could trigger a higher susceptibility for epilepsy or development of mental disorders. We addressed the early developmental actions of an IL-6 type pro-inflammatory cytokine, leukemia inhibitory factor (LIF) on cortical maturation both in vivo and in slice cultures. A rather modest enhancement of LIF signaling was used as a proxy for an early postnatal inflammation. It resulted in a dramatic interneuron synaptopathy. Our results indicate that LIF impairs development of cortical interneuron subsets and causes a lasting imbalance of excitation and inhibition. In particular, LIF not only downregulates the expression of the TrkB receptor ligand NT4, but concurrently prevents the neurotrophins from activating the MAP kinase pathway. As a consequence, strictly TrkB-dependent cortical inhibitory GABA-ergic interneurons, in particular fast-spiking basket (B) and chandelier (C) neurons are severely affected. They display an underdevelopment of the somatodendritic domain, less and smaller presynaptic boutons, a reduced expression of the calcium buffer parvalbumin, the voltage-gated potassium channel Kv3.2, the ultrafast vesicular calcium sensor synaptotagmin-2, and glutamate decarboxylase isoform GAD-65 which synthesized GABA for phasic inhibition. These presynaptic proteins are essential for the fast-spiking properties and a highly synchronous GABA release, both being critical determinants for neuronal oscillations in the cognitive gamma frequency band. Also pyramidal cells are altered: dendritic spines are lower in density and less mature, GABAA R α 1 at basket cell terminals and α 2 at chandelier cell terminals are reduced in expression, the axon initial segment is shorter and its core scaffolding protein ßIV-spectrin is reduced. The presynaptic deficits (outlined in the graphical abstract with left: healthy; right: LIF / inflammation) suggest a serious impairment of inhibition, and calcium imaging indeed reveals a hyperexcitable network. A set of recovery experiments reveals a surprisingly slow recovery of the affected proteins, and intriguingly, synaptotagmin-2 entirely fails to recover. In summary, our study suggests LIF as a negative upstream modulator of TrkB signaling. The impaired trophic support results in a maldevelopment in particular of fast-spiking interneurons, a deficit of inhibition and cortical hyperexcitability.